Implementasi Nilai-Nilai Hijrah Nabi dalam Pembentukan Karakter Anak - Muhammad Zidni Ilman (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
History records that, during its development, Islam, while led by the Prophet, carried out the Hijrah 4 times in 3 different places. Hijrah means moving a people from unpleasant or sad conditions to a pleasant place. Hijrah was legalized on the basis of Allah's command for the reason of avoiding the torture and pressure carried out by the Mushrikin of Mekkah against the Muslims of Mekkah. However, during the Hijrah process, not all places welcomed the arrival of Muslims from Mecca, there were also those who accepted them gracefully without any particular conditions, there were also those who rejected them and even went so far as to torture them. This Hijrah education needs to be a concern for us, so that we are able to know that in life, if you want to achieve maximum results, great success, you need great sacrifices. To support this research, the methodology the author uses is library research. The results of this research are that the brilliant success achieved by the Prophet in preaching was not obtained from instant results, there were struggles that drained energy, there were also feelings that were also heart-wrenching, and all of this certainly has a lot of educational value that we can take away, and also there are lessons that we can apply both as educators and students.